Image-based identification and genomic analysis of single circulating tumor cells in high grade serous Ovarian Cancer patients - Salmon, Carolin; Levermann, Janina; Neves, Rui P. L.; Liffers, Sven-Thorsten; Kuhlmann, Jan Dominik; Buderath, Paul; Kimmig, Rainer; Kasimir-Bauer, Sabine (Cancers, 2021)
In Ovarian Cancer (OC), the analysis of single circulating tumor cells (sCTCs) might help to investigate genetic tumor evolution during the course of treatment. Since common CTC identification features failed to reliably detect CTCs in OC, we here present a workflow for their detection and genomic analysis. Blood of 13 high-grade serous primary OC patients was analyzed, using negative immunomagnetic enrichment, followed by immunofluorescence staining and imaging for Hoechst, ERCC1, CD45, CD11b and cytokeratin (CK) and sCTC sorting with the DEPArrayTM NxT. The whole genome of single cells was amplified and profiled for copy number variation (CNV). We detected: Type A-cells, epithelial (Hoechstpos, ERCC1pos, CD45neg, CD11bpos, CKpos); Type B-cells, potentially epithelial (Hoechstpos, ERCC1pos, CD45neg, CD11bpos, CKneg) and Type C-cells, potentially mesenchymal (Hoechstpos, ERCC1pos, CD45neg, CD11bneg, CKneg). In total, we identified five (38.5%) patients harboring sCTCs with an altered CN profile, which were mainly Type A-cells (80%). In addition to inter-and intra-patient genomic heterogeneity, high numbers of Type B- and C-cells were identified in every patient with their aberrant character only confirmed in 6.25% and 4.76% of cases. Further identification markers and studies in the course of treatment are under way to expand sCTC analysis for the identification of tumor evolution in OC.